First line vasoactive therapy after fluid resuscitation in pediatric septic shock - Dopamine, Adrenaline or Noradrenaline? - Mehak Bansal; Praveen Khilnani (Wolters Kluwer Medknow Publications, 2019)
Severe sepsis and septic shock are the leading cause of morbidity and mortality in children all over the world, in both developed and developing nations. Surviving Sepsis Guidelines 2016 have recommended norepinephrine as the first choice of vasoactive agent in adult septic shock flowed by adrenaline or vasopressin in cases who do not respond to norepinephrine. In this article we have reviewed the literature and compared noradrenaline and adrenaline as first line vasoactive drug in children with fluid refractory septic shock. We have also discussed the change in the paradigm -use of dopamine as alternative instead of first line vasoactive agent